Investigation of Common Compounds in High Grade and Low Grade Aquilaria Malaccensis using Correlation Analysis - Nurlaila, Ismail; Mohd Hezri Fazalul, Rahiman; Rozita, Jailani; Nor Azah, Mohd Ali; Mohd Nasir, Taib; Saiful Nizam, Tajuddin (IEEE, 2012)
This paper presents a correlation analysis between high grade and low grade of Aquilaria Malaccensis (AM). Seven selected samples of AM were identified using Gas Chromatograph – Mass Spectra (GC-MS) and several statistical techniques have been employed. The samples were separated into two grades such as high grade and low grade. The analysis involves of normality test such as Shapiro Wilk, standard deviation, skewness, kurtosis and correlation analysis. All the analysis was done using SPSS ver. 15.0. The result shows that there are no significant correlation between high grade and low grade and it is a high correlation among compounds in similar grade. Three common compounds and highly correlated found in both grade and they are hexadecanoic acid, valencene and α-guaiene.